Kajian Posisi Bahan Setek Batang Dan Dosis Rootone-F Pada Perbanyakan Tanaman Markisa Kuning (Passiflora edulis var. flavicarpa) - I PUTU EKO SURYA ARIANTA; I PUTU DHARMA; I WAYAN WIRAATMAJA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2021)
Study of Stem Position Cuttings and Rootone-F Dosage for Yellow Passion Fruit Propagation (Passiflora edulis var. flavicarpa) Yellow passion fruit (Passiflora edulis var. Flavicarpa) is a type of sour passion fruit that is generally grown in low to medium plains. This passion fruit has an oval round shape, yellow when ripe and green when young. Mostly the yellow passion fruit was propagated sexually by seed, while vegetative methods can be done by means of connection, cuttings and tissue culture. Passion fruit propagation is easier and faster to cloned than other vegetative propagation methods. The focus to know the different result of stem position treatment and administration of Rootone-F growth regulator and its interaction on the growth of yellow passion fruit cuttings. This study used a 2-factor factorial design, namely: treatment of stem position and administration of Rootone-F growth regulator. The observed variables were shoot growth time, shoot oven dry weight, shoot length, primary root number, primary root length, root oven dry weight, number of leaves, leaf area, leaf oven dry weight, total wet weight, total oven dry weight. The results showed that the highest root oven dry weight was obtained in the treatment at the base of the stem with a dose of Rootone-F 225 mg / cuttings (P3Z3) with a root oven dry weight of 3.30 grams.